(NrIFTOWYE STRUKTURY wOSTO^NOJ aFRIKI (B- (NRASKOL KONTINENTA I ZAROVDENIE OKEANA (B/s - (NkAZXMIN(B, (NwLADIMIR gRIGORXEWI^s; (NzONEN[AJN(B, (Nl(B.(Np(B.s ((NmOSKWA (B:s (NnAUKA(B,s, 1987)
(NbIBLIOGR(B.: (NS(B. 192-204s
(Nan sssr(B, (NiN(B-(NT OKEANOLOGII IM(B. (Np(B.(Np(B. (N{IR[OWAs
Keywords: (NrAZLOMY GLUBINNYE (B- (NwOSTO^NAQ aFRIKAs